Does the Christian worldview provide a place for the law of attraction? (Part 2): An apologetic evaluation of the way the Bible is used in promoting this idea - Maritz, Daniël J.; Stoker, Henk G. (Verbum et Ecclesia, 2016)
This article investigates the biblical motivation that is given for the secular idea of the so-called spiritual law of attraction to become part of Christian doctrine. In 2010 Pastor At Boshoff of the Christian Revival Church (CRC) preached two sermons on the law of attraction in which he claimed it as a powerful principle in the Word of God. According to him this biblical ‘law’ provides human beings with physical manifestations of their thoughts and words. The idea to create one’s own favourable future through the law of attraction flows from a New Age worldview and is similar to the positive confession doctrine taught by popular Word of Faith teachers. Boshoff’s claim regarding the law of attraction cannot be deduced from the key Scripture passages he uses, which reflects an unfounded use of Scripture to promote this idea. Intradisciplinary and/or interdisciplinary implications: The article challenges the secular infiltration of the Law of Attraction in the church. This is important since the so-called Law of Attraction was preached by Pastor A. Boshoff of the CRC. Many of his listeners embrace his teaching although it reflects a poor exposition and application of Scripture.
free